Forms of unfreedom in the Medieval Mediterranean - Barros, Maria Filomena Lopes de; Almagro Vidal, Clara (Biblioteca - Estudos & Colóquios, 2021)
Dependence and loss of freedom - be it partial or total - go hand in hand. During the Middle Ages, people were bonded together through a wide variety of ties that limited their freedom in different ways and to variable degrees.This volume explores these forms of unfreedom. Focusing on both the Iberian Peninsula and the Mediterranean from the eighth century until the fifteenth, the contributors focus on aspects such as transformations of terminology, implementation of different legal traditions across time and space, establishment and dissolution of bonds, and details of everyday life attached to these situations. Looking at the "ties that bind", that is, the obligations acquired and everyday implications of the establishment of that dependence, this volume reflects on concepts such as captivity, slavery, manumission and serfdom, among others, and their appearance in the sources.